2018
DOI: 10.2298/jsc180131044k
|View full text |Cite
|
Sign up to set email alerts
|

Visible light absorption of TiO2 nanoparticles surface-modified with vitamin B6: A comparative experimental and DFT study

Abstract: Surface modification of titanium dioxide nanoparticles (TiO 2 NPs) with the biologically active molecule pyridoxine hydrochloride (vitamin B 6) was found to alter the optical properties. Microstructural characterization involving transmission electron microscopy (TEM) and X-ray diffraction (XRD) analysis revealed that the anatase TiO 2 NPs had a narrow size distribution with an average diameter of 45 Å. The absorption onset of the surface-modified TiO 2 samples was red-shifted by about 0.4 eV compared to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For example, the most studied photocatalyst TiO 2 has a band gap of 3.2 eV and, therefore, absorbs less than 5% of the available solar light, allowing only UV photons to produce electron–hole pairs and stimulate redox processes on the catalyst surface. During the last decade, extensive research has shown that interfacial charge transfer (ICT) complex formation between inorganic semiconductors, anatase TiO 2 , in particular, and small colorless aromatic compounds leads to the appearance of the absorption in the more practical, visible or near-infrared spectral range. Direct electron transfer across the organic–inorganic interfaces has new potential applications in different areas such as photocatalysis, ,, photovoltaics, , , , and sensing of small colorless biomolecules including drugs. ,, Moreover, proper functionalization can increase the sorption capacity and selectivity of sorbents toward heavy metal ions, while the presence of bioactive molecules on the particles’ surfaces decreases their toxicity. , …”
Section: Introductionmentioning
confidence: 99%
“…For example, the most studied photocatalyst TiO 2 has a band gap of 3.2 eV and, therefore, absorbs less than 5% of the available solar light, allowing only UV photons to produce electron–hole pairs and stimulate redox processes on the catalyst surface. During the last decade, extensive research has shown that interfacial charge transfer (ICT) complex formation between inorganic semiconductors, anatase TiO 2 , in particular, and small colorless aromatic compounds leads to the appearance of the absorption in the more practical, visible or near-infrared spectral range. Direct electron transfer across the organic–inorganic interfaces has new potential applications in different areas such as photocatalysis, ,, photovoltaics, , , , and sensing of small colorless biomolecules including drugs. ,, Moreover, proper functionalization can increase the sorption capacity and selectivity of sorbents toward heavy metal ions, while the presence of bioactive molecules on the particles’ surfaces decreases their toxicity. , …”
Section: Introductionmentioning
confidence: 99%